The roots of Tantra - Harper, Katherine Anne; Brown, Robert L. (SUNY series in tantric studies, 2002)
Machine generated contents note:pt. IOverviews --1.What Do We Mean by Tantrism? /Andre Padoux --2.Early Evidence for Tantric Religion /David N. Lorenzen --pt. IIHistory and Development of Tantra --3.Historical and Iconographic Aspects of Sakta Tantrism /M.C. Joshi --4.Auspicious Fragments and Uncertain Wisdom: The Roots of Srividya Sakta Tantrism in South India /Douglas Renfrew Brooks --5.Structural Interplay of Tantra, Vedanta, and Bhakti: Nondualist Commentary on the Goddess /Thomas B. Coburn --pt. IIIArt History and Archaeology of Tantra --6.Spinal Serpent /Thomas McEvilley --7.Warring Saktis: A Paradigm for Gupta Conquests /Katherine Anne Harper --8.Early Evidence of the Pancaratra Agama /Dennis Hudson --pt. IVVedas and Tantra --9.Imagery of the Self from Veda to Tantra /Teun Goudriaan --10.Tongues of Flame: Homologies in the Tantric Homa /Richard K. Payne --pt. VTexts and Tantra --11.Becoming Bhairava: Meditative Vision in Abhinavagupta's Paratrisika-laghuvrtti /Paul E. Muller-Ortega --12.Tantric Incantation in the Devi Purana: The Padamala Mantra Vidya /Lina Gupta.